2020
DOI: 10.1021/acsomega.0c02865
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the C-Terminal Tail of RecA Proteins from Alkaline pH-Resistant Bacterium Deinococcus Ficus

Abstract: Deinococcus ficus CC - FR2 - 10T , resistant to ultraviolet, ionizing radiation, and chemicals which may cause DNA damage, was identified in Taiwan. The expression level of D. ficus RecA, which has 92% sequence identity with Deinococcus radiodurans ( Dr. ) RecA, will be upregulated upon UV radiation. Multiple sequence alignment of RecA proteins from bacteria belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…A chimeric RecA, D. ficus C17 E. coli RecA (in which the C-terminus was replaced with the corresponding residues in the C-terminus of E. coli RecA), was constructed and purified. Interestingly, the pH-reaction profile of RecA-mediated strand exchange shifted to acidic conditions for D. ficus C17 E. coli RecA (29). These observations highlight the influence of the C-terminus of RecA proteins on the DNA strand-exchange reaction.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…A chimeric RecA, D. ficus C17 E. coli RecA (in which the C-terminus was replaced with the corresponding residues in the C-terminus of E. coli RecA), was constructed and purified. Interestingly, the pH-reaction profile of RecA-mediated strand exchange shifted to acidic conditions for D. ficus C17 E. coli RecA (29). These observations highlight the influence of the C-terminus of RecA proteins on the DNA strand-exchange reaction.…”
Section: Introductionmentioning
confidence: 78%
“…For E. coli RecA, the formation of nucleoprotein filaments is relatively slow and exhibits high proton dependence. The rate-limiting step of DNA strand exchange is the formation of nucleoprotein filaments for E. coli RecA, and the reaction optimum is near pH 7.0 (29,49). In a previous study, Lusetti et al reported that progressively removing C-terminal residues from E. coli RecA proteins will cause a progressive shift in the pH-reaction profile of RecA-induced DNA strand exchange and result in strong inhibition of DNA strand exchange %pH 7.0 (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations